Qualidade de vida em mulheres na pós-menopausa, usuárias e não usuárias de terapia hormonal - Martins, Marcelo Antonio Domingos [UNESP]; Nahas, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge [UNESP]; Uemura, Gilberto [UNESP]; Buttros, Davi de Araújo Bitro [UNESP]; Traiman, Paulo [UNESP] (My University, 2009)
PURPOSE: to evaluate the quality of life of post-menopause women, users and non-users of hormonal therapy (HT), in a Healthcare Unit in Franca, São Paulo, Brazil. METHODS: a clinical transversal study, carried out with 250 post-menopausal women, with ages from 45 to 70 years old, attended to in Healthcare Units, from September 2007 to August 2008. Participants were divided into two groups: HT users (n=70) and non-users (n=180). Women making continuous HT use for at least six months were considered as users. Sociodemographic and clinical characteristics have been evaluated. Blatt-Kupperman's menopausal index has been applied to assess climacteric symptoms, and the Women's Health Questionnaire (WHQ), to assess their quality of life. Fisher's exact test or χ2 and Mann-Whitney and Kruskal-Wallis's tests have been used for the statistical analysis. RESULTS: no significant difference has been found in the comparison of groups, concerning age, menarche, menopause, parity and body mass index. It has been seen that 67.2% of the women were married, 83.2% had attended primary school and 53.2% were housewives, with no difference between the groups. HT users reported lower frequency of climacteric symptoms (BKMI) with moderate and marked intensity, as compared to non-users (p<0.001). Even though HT users presented lower average score in cognitive deficit (p<0.001), vasomotor symptoms (p=0.04), sleeping problems (p<0.001), attractiveness (p=0.02) from the WHQ, there has been no difference in the total score, as compared to non-users. CONCLUSIONS: post-menopausal women, HT users and non-users, admitted at Healthcare Units, have not presented differences in global quality of life.
Quality of life in postmenopausal women, users and non-users of hormone therapy
Keywords: Estrogen replacement therapy; Hormonal therapy replacement; Menopause; Quality of life; Questionnaires; Women's health